Synthesis and Antimicrobial Activity of Some 3-(5-Phenyl-4,5-dihydro-1-substitutedpyrazol-3-yl) chromen-2-one - B. Lakshminarayanan; V. Rajamanickam; T. Subburaju; L. A. Pradeep Rajkumar (E-Journal of Chemistry)
The title compounds were synthesized by condensation of 3-acetyl chromen-2-one with benzaldehyde in presence of alcoholic sodium hydroxide to get intermediate 3-(3-phenyl acryloyl) chromen-2-one, which were further treated with hydrazine hydrate to get 3-(5-phenyl-4,5-dihydro-1H-pyrazol-3-yl) chromen-2-one. The latter were refluxed with various amino compounds and various aldehyde derivatives on water bath for 5 h to afford title compounds. All the compounds were tested for their antibacterial and antifungal activities by the cup plate method.